L’entre-deux comme résilience. Les relocalisations sur le volcan merapi (Java) - Jean-Baptiste Bing (Carnets de Géographes, 2014)
After their villages were destroyed by the eruption of October and November 2010, several village communities of the Mount Merapi’s southern flank were relocated outside the main hazard zone. Elaborated by authorities in collaboration with representatives of the inhabitants, these operations caused and cause delicate socio-cultural problems about everyday life as about the complex relationships between population and its mountain, against a background of a long term mutation in economics and metaphysics linked to modernity. Written at the request of representatives from a local “hybrid forum”, this article proposes to examine the situation of relocated villages, seeing them as between-spaces in order to link issues of representation, of territoriality and of economics at short and middle term. This article concludes with the necessity of interdisciplinarity for analysis as for action, organized as closely as possible to the inhabitants and coordinated with them, in order to face the multiplicity of challenges at several spatial and temporal scales.